Diversity and antioxidant activity of Trametes Fr. in Malaysia / Noraswati Mohd Nor Rashid - Mohd Nor Rashid, Noraswati (2010)
Research on antioxidant properties as a natural antioxidant, particularly in polypores, have been widely done since the past decade. It is known that antioxidant capacity is essential in protecting organisms and cells from damage brought on by oxidative which is believed to be the cause for ageing and degenerative diseases. In this study, biodiversity and antioxidant activity of Malaysian Trametes spp. which is from the group of polypores were investigated. Polypores were collected in Peninsular Malaysia forests from the year 2006 until 2007. The species were identified by taxonomic keys based on macromorphology and micromorphology analysis. Trametes hirsuta, T. pocas, T. lactinea, T. menziezii and T. feei were identified throughout the collection.Methanolic and dichloromethane extracts of mycelia of Trametes spp. were analysed for antioxidant activity on 1,1-diphenyl-2-picrylhdrazyl (DPPH) radicals and reducing ability of CUPRAC assay. Furthermore, the total of phenolic content of methanol extracts of Trametes spp. was analysed and the relationship of the phenol contents with the antioxidant activity was observed. IC50 values of scavenging effect on DPPH radicals of methanolic extracts of Trametes spp. ranging from 7.296 to 27.324 mg/ml and dichloromethane extracts ranging from 36.2 to 66 mg/ml, respectively. The reducing ability of Trametes spp. ranging from 0.3457 to 0.5367 at 0.5 mg/ml. Total phenolic content of methanolic extracts of Trametes spp. ranging from 10.54 to 23.28 mg/g extract.A good correlation was found between total phenolic content of Trametes spp.methanolic extracts on CUPRAC assay (r2 = 0.9546) with antioxidant properties. However, a weak correlation was found between the scavenging effects on DPPH radicals of the methanolic extracts with the total phenolic content in Trametes spp. methanolic extracts (r2 = 0.1332). These results show that both phenolic and nonii phenolic components were responsible for the total antioxidative activity of the Trametes spp. extracts. Therefore, Trametes spp. can be a natural source of antioxidants.